Synthesis, characterization and catalytic properties for the ethanol transformation of La-Mg hydrotalcites. - Ballesteros-Plata, Daniel; Cecilia-Buenestado, Juan Antonio; Barroso-Martín, Isabel; Infantes-Molina, Antonia; Balestra, Giulia; Tabanelli, Tomasso; López Nieto, José Manuel; Montaña, Maia; Rodríguez-Castellón, Enrique (My University, 2023)
Ethylene is considered a key feedstock for the chemical industry because it is possible to obtain a wide range of products such as ethylene oxide, ethylbenzene, 1,2-dichloroethane, polyethylene resin, ethylene glycol, among others [1]. Traditionally, ethylene has been synthesized by steam cracking, however, this process requires a high-energy cost. Therefore, it is necessary to develop an alternative process that is less expensive and friendly to the environment. In this sense, it is possible to obtain ethylene from the dehydration reaction of ethanol produced in sugar platforms for the transformation of lignocellulosic biomass from agricultural waste [2]. In this work, MgO/La2O3 catalysts with different Mg/La molar ratios have been prepared. All the catalysts had been calcined at 600ºC/3h with a heating ramp of 2ºC/min. The catalysts were tested in the reaction system to study their activity in the ethanol gas-phase conversion. The catalysts were characterized by XPS, XRD, TEM-EDX, CNH analysis, adsorption-desorption of N2 at -196 ºC, NH3-TPD and CO2-TPD. With the increase in the amount of La, the catalytic activity increased from an ethanol conversion of 20.4% over MgO to 84.2% on the Mg/La=1 mixed oxide (Table 1). The ethylene selectivity increased with the La amount, going from 16% over the MgO catalyst to 87% over the mixed oxide with a Mg/La=1 molar ratio. It was verified for the Mg/La=3 sample that by decreasing the temperature from 400 to 350 ºC there was a drastic decrease in the EtOH conversion, from 75.4% to 20.2%, respectively. In this case, ethylene was again the main product and its selectivity increased from 51.9% to 77.6%.
Keywords: Etileno - Industria; Industria química; Ethylene; Magnesium; Lanthanum; Guerbet